Variations of CM chondrites evaluated from X-ray diffraction - Imae, Naoya; Kimura, Makoto (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object